Identification and characterization of Colletotrichum fioriniae and C. fructicola that cause anthracnose in pecan - Chang, Jun; Zhai, Fengyan; Zhang, Yabo; Wang, Di; Shu, Jinping; Yao, Xiaohua (Frontiers in Plant Science, 2022)
Pecan (Carya illinoinensis Wang. K. Koch) is a deciduous tree of the Juglandaceae family with important economic value worldwide. Anthracnose of the pecan leaves and shuck is a devastating disease faced by pecan-growing areas in China. However, the causal species occurring on pecan remain largely unidentified. we collected samples of diseased pecan from the provinces of China, Leaves and fruits affected by anthracnose were sampled and subjected to fungus isolation, The morphological characters of all strains were observed and compared; Multi-locus phylogenetic analyses [Internally transcribed spacer (ITS), Actin (ACT), Calmodulin (CAL), Chitin synthase (CHS1), Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and b-tubulin (TUB2)] were performed on selected representative strains; examine their pathogenicity on leaves of pecan.The results showed that: (1) resulting in a total of 11 Colletotrichum isolates, Two Colletotrichum species were identifified to be C. fioriniae and C. fructicola; (2) Pathogenicity tests revealed that both species caused black spots on pecan leaves and fruit, The virulence of the different isolates varied substantially, with C. fioriniae PCJD179 being the most virulent; (3) The susceptibility levels of pecan tree varieties, ‘Mahan’ and ‘Kanza’, were determined, No significant differences were observed in the lesion sizes produced by the various isolates in ‘Kanza’, while there were signifificant differences in ‘Mahan’. This study is thefifirst to determine that C. fructicola and C. fioriniaecan cause anthracnose in pecan in China. It improves the understanding of the species that cause anthracnose in pecan and provides useful information for the effective control of this disease in China.